Answer:
6.0666
Step-by-step explanation:
273÷45=6.0666
Answer:
see explanation
Step-by-step explanation:
Given
(a + b - 2)(a - b + 2)
Each term in the second factor is multiplied by each term in the first factor, that is
a(a - b + 2) + b(a - b + 2) - 2(a - b + 2) ← distribute the parenthesis
= a² - ab + 2a + ab - b² + 2b - 2a + 2b - 4 ← collect like terms
= a² - b² +4b - 4
Answer:
Additive inverse : j(x) = -x + 24
Multiplicative inverse : k(x) = 1/x-24
Step-by-step explanation:
I literally have no idea how, I got this answer off of quizlet :) have a good day.
V = 1/3 l h w
V = 1/3 (12)(15)(9)
V= = 540
answer 540 m^3
Answer:
False
Step-by-step explanation:
To solve this problem, plug in the value for Y, 9, into the inequality.
9 + 3 < 12
Now, solve the inequality. Evaluating 9 + 3, the equation becomes:
12 < 12
12 is not less than 12 (12 = 12), therefore the answer is false.